1999
DOI: 10.1002/hep.510300610
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of hepatitis C virus quasispecies in patients with severe cholestatic hepatitis after liver transplantation

Abstract: Evolution of hepatitis C quasispecies may be one mechanism by which fibrosing cholestatic hepatitis develops after liver transplantation. In this study, we compared changes in quasispecies complexity and/or divergence in (1) hepatitis C-infected immunosuppressed transplant recipients and in immunocompetent controls; (2) transplant recipients with mild recurrence, and in those with the most severe form of posttransplantation recurrence. Quasispecies were measured in 12 hepatitis C-infected patients pretransplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 37 publications
3
55
0
Order By: Relevance
“…Patients with rapidly progressive cholestatic hepatitis seem to have very high levels of HCV RNA, more than 10-fold greater than the average patient with recurrent HCV, fewer quasispecies, and reduced lymphocyte recognition of HCV antigens. [9][10][11][42][43][44][45][46][47] These observations support a scenario in which the immune response to HCV is reduced, and in which the virus can proliferate rapidly without mutations. It is therefore important to note that most cases of rapidly progressive cholestatic hepatitis C seem to develop after treatment of presumed acute rejection with either monoclonal antibodies or high-dose bolus corticosteroids.…”
Section: Rapidly Progressive Cholestatic Hepatitis Csupporting
confidence: 61%
“…Patients with rapidly progressive cholestatic hepatitis seem to have very high levels of HCV RNA, more than 10-fold greater than the average patient with recurrent HCV, fewer quasispecies, and reduced lymphocyte recognition of HCV antigens. [9][10][11][42][43][44][45][46][47] These observations support a scenario in which the immune response to HCV is reduced, and in which the virus can proliferate rapidly without mutations. It is therefore important to note that most cases of rapidly progressive cholestatic hepatitis C seem to develop after treatment of presumed acute rejection with either monoclonal antibodies or high-dose bolus corticosteroids.…”
Section: Rapidly Progressive Cholestatic Hepatitis Csupporting
confidence: 61%
“…37 In contrast, Sullivan et al found no differences in complexity at baseline between patients with mild or severe HCV recurrence. 35 The latter study also is in contrast with the report by Pessoa et al concerning HCV quasispecies evolution in OLT patients who develop fibrosing cholestatic hepatitis, 11 perhaps because that form of severe HCV recurrence is a completely different pathologic condition. Sanchez-Fueyo et al found that, although quasispecies complexity in the HVR-1 was similar in both OLT patients with mild or severe HCV recurrence, amino acid changes were significantly more frequent and the dN/dS ratios higher in patients with mild HCV recurrence after OLT.…”
Section: Discussionmentioning
confidence: 84%
“…[6][7][8][9] In the liver transplantation setting, some studies have also analyzed the effect of the heterogeneity in the envelope region of HCV, with discrepant results. 10,11 In contrast, the potential influence of viral variability in T-cell epitopes on the outcome of recurrent infection after transplantation has been explored only rarely. Among the relevant human leukocyte antigen (HLA)-A2-restricted T-cell epitopes mapped in the HCV polyprotein, those in the NS3 protein are commonly recognized by CD8-positive T-cells in the peripheral blood [12][13][14] and liver [14][15][16] of chronically infected patients.…”
Section: H Epatitis C Virus (Hcv) Infection Is Distributedmentioning
confidence: 99%
“…Our results show that in the context of a new environment and transplant related factors, which include immunosuppression and a new liver, the genetic codes of both CD 81 binding regions are kept relatively stable. Other regions of the HCV genetic code, such as hypervariable region 1 (HVR1), NS2 and NS3 have been reported to undergo considerable variability as soon as a few months after liver transplantation [19][20][21].…”
Section: Discussionmentioning
confidence: 99%